Effects of Mangiferin on LPS-Induced Inflammation and SARS-CoV-2 Viral Adsorption in Human Lung Cells - Mariarita Spampinato; Giuseppe Carota; Giuseppe Sferrazzo; Virginia Fuochi; Alfio Distefano; Simone Ronsisvalle; Federica Sipala; Rosario Giuffrida; Pio Maria Furneri; Michelino Di Rosa; Daniele Tibullo; Giovanni Li Volti; et al. (MDPI AG, 2022)
The growing interest in natural bioactive molecules, as an approach to many pathological contexts, is widely justified by the necessity to overcome the disadvantageous benefit-risk ratio related to traditional therapies. Among them, mangiferin (MGF) shows promising beneficial properties such as antioxidant, anti-inflammatory, and immunomodulatory effects. In this study, we aimed to investigate the antioxidant and anti-inflammatory properties of MGF on lipopolysaccharide (LPS)-induced lung NCI-H292 cells, focusing on its role against COVID-19 adsorption. In order to obtain this information, cells treated with LPS, with or without MGF, were analyzed performing wound healing, gene expression of inflammatory cytokines, GSH quantification, and JC-1 staining. Moreover, the inhibition of viral adsorption was evaluated microbiologically and the results were further confirmed by molecular docking analysis. In this regard, MGF downregulates the expression of several inflammatory factors, enhances GSH levels, promotes the wound healing rate, and restores the mitochondrial dysfunction caused by LPS. In addition, MGF significantly inhibits SARS-CoV-2 adsorption as shown by the gene expression of ACE2 and TMPRSS-2, and furtherly confirmed by microbiological and molecular modeling evaluation. Although more investigations are still needed, all data obtained constitute a solid background, demonstrating the cytoprotective role of MGF in inflammatory mechanisms including COVID-19 infection.